2018
DOI: 10.2147/tcrm.s183200
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of heart failure symptoms, disease severity, treatment decision-making and side effects by patients and cardiologists: a multinational survey in a cardiology setting

Abstract: PurposeExplore the extent to which heart failure (HF) symptoms and side effects of HF treatment experienced by patients are recognized by cardiologists, and concordance between patient–cardiologist perceptions of HF severity and patients’ contributions to treatment decision-making.MethodsA multinational, cross-sectional survey of cardiologists and patients with HF was conducted. Patient-record forms (PRFs) were completed by cardiologists for consecutive consulting patients with HF, who completed a patient self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The baseline characteristics and comorbidities were consistent with those of other surveys/cross-sectional studies on chronic HF patients from Europe, as well as with those of other DSP™ HF studies. [31][32][33][34][35] The occurrence of common and most troublesome symptoms was also in line with that in previous studies. 36 The five most troublesome symptoms reported by the patients correlated with the most frequently reported symptoms, with the exception of shortness of breath when at rest, which frequently bothered patients despite not being the most common symptom.…”
Section: Discussionsupporting
confidence: 88%
“…The baseline characteristics and comorbidities were consistent with those of other surveys/cross-sectional studies on chronic HF patients from Europe, as well as with those of other DSP™ HF studies. [31][32][33][34][35] The occurrence of common and most troublesome symptoms was also in line with that in previous studies. 36 The five most troublesome symptoms reported by the patients correlated with the most frequently reported symptoms, with the exception of shortness of breath when at rest, which frequently bothered patients despite not being the most common symptom.…”
Section: Discussionsupporting
confidence: 88%
“…Although most cardiologists find a discussion of the prognosis in HF important, the majority is reluctant to broach the topic at the time of diagnosis [ 26 ]. In addition, a multicontinental cross-sectional survey of more than two thousand patient-cardiologist pairs indicated that they often understate the severity of HF and neglect to discuss treatment choice with almost a third of patients [ 27 ]. This reluctance to discuss the diagnosis and prognosis of HF with patients likely contributes to a notoriously low sensitivity of both self-reported HF and concordance of patient awareness with physicians’ assessment of disease severity [ 28 – 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected from the Adelphi HF Disease Specific Programme TM (DSP), 14 a cross-sectional survey of physicians and their HF patients conducted in a real-world setting in Japan between February and July 2016. 15 The DSP comprises 3 main phases: a preparatory phase involving the development of survey materials and participant recruitment, a data-collection phase, and data analysis. Details of these 3 phases have been described previously.…”
Section: Methodsmentioning
confidence: 99%